Antioxidant activity of leaves of Calophyllum Rubiginosum - Bakhtiar, M. Taher; Darnis, Deny Susanti; Arief Ichwan, Solachuddin Jauhari; Ahmad, Farediah (Science Publications, 2010)
Calophyllum species have been used in traditional medicine for their therapeutic values for many years. This use was explained by several previous studies where antimicrobial, antifungal, anti-HIV and anti-cancer and antioxidant compounds were isolated from several Calophyllum species. Approach: The leaves were extracted with n-hexane (hexane), dichloromethane (DCM) and methanol using soxhlet apparatus. Total phenolic contents of each extract were evaluated using Folin Ciocalteau Reagent (FRC) while Ferric Thiocyanate (FTC) and 2,2-Diphenyl-1 Picrylhydrazyl (DPPH) were used for lipid peroxidation and free radical scavenging activity respectively. Results: As the results, methanol extracts (5 mg mL-1) has higher phenolic contents of 66.2 μg mg-1 Gallic Acid Equivalent (GAE) compared to n-hexane and DCM extracts with phenolic content of 50.5 and 52.5 μg mg-1 GAE respectively. In FTC method, methanol had the lower absorbance values which indicate high antioxidant activities. In DPPH radical scavenging test however, DCM extract showed high antioxidant activity with an IC50 value of 0.11mg mL-1, followed by methanol and hexane with IC50 values of 0.23 and 4.5 mg mL-1 respectively. The IC50 of standards were 0.74 and 0.56 mg mL-1 for ascorbic acid and α tocopherol, respectively. Conclusion: Finally, the positive outcome of the research can be further tested in the future to ascertain the active compound of the leaves of C. rubiginosum.